Climate and air quality impacts due to mitigation of non-methane near-term climate forcers - R. J. Allen; S. Turnock; P. Nabat; D. Neubauer; U. Lohmann; D. Olivié; N. Oshima; M. Michou; T. Wu; J. Zhang; T. Takemura; M. Schulz; et al. (Atmospheric Chemistry and Physics, 2020)
It is important to understand how future environmental policies will impact both climate change and air pollution. Although targeting near-term climate forcers (NTCFs), defined here as aerosols, tropospheric ozone, and precursor gases, should improve air quality, NTCF reductions will also impact climate. Prior assessments of the impact of NTCF mitigation on air quality and climate have been limited. This is related to the idealized nature of some prior studies, simplified treatment of aerosols and chemically reactive gases, as well as a lack of a sufficiently large number of models to quantify model diversity and robust responses. Here, we quantify the 2015–2055 climate and air quality effects of non-methane NTCFs using nine state-of-the-art chemistry–climate model simulations conducted for the Aerosol and Chemistry Model Intercomparison Project (AerChemMIP). Simulations are driven by two future scenarios featuring similar increases in greenhouse gases (GHGs) but with “weak” (SSP3-7.0) versus “strong” (SSP3-7.0-lowNTCF) levels of air quality control measures. As SSP3-7.0 lacks climate policy and has the highest levels of NTCFs, our results (e.g., surface warming) represent an upper bound. Unsurprisingly, we find significant improvements in air quality under NTCF mitigation (strong versus weak air quality controls). Surface fine particulate matter (PM2.5) and ozone (O3) decrease by -2.2±0.32<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="58pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="e7d1e4510ab8d9bb4ca42781032653c5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-20-9641-2020-ie00001.svg" width="58pt" height="10pt" src="acp-20-9641-2020-ie00001.png"/></svg:svg> µg m−3 and -4.6±0.88<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="58pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="43a101e9a2dd921e24c5cb40f6eb38ea"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-20-9641-2020-ie00002.svg" width="58pt" height="10pt" src="acp-20-9641-2020-ie00002.png"/></svg:svg> ppb, respectively (changes quoted here are for the entire 2015–2055 time period; uncertainty represents the 95 % confidence interval), over global land surfaces, with larger reductions in some regions including south and southeast Asia. Non-methane NTCF mitigation, however, leads to additional climate change due to the removal of aerosol which causes a net warming effect, including global mean surface temperature and precipitation increases of 0.25±0.12 K and 0.03±0.012 mm d−1, respectively. Similarly, increases in extreme weather indices, including the hottest and wettest days, also occur. Regionally, the largest warming and wetting occurs over Asia, including central and north Asia (0.66±0.20 K and 0.03±0.02 mm d−1), south Asia (0.47±0.16 K and 0.17±0.09 mm d−1), and east Asia (0.46±0.20 K and 0.15±0.06 mm d−1). Relatively large warming and wetting of the Arctic also occur at 0.59±0.36 K and 0.04±0.02 mm d−1, respectively. Similar surface warming occurs in model simulations with aerosol-only mitigation, implying weak cooling due to ozone reductions. Our findings suggest that future policies that aggressively target non-methane NTCF reductions will improve air quality but will lead to additional surface warming, particularly in Asia and the Arctic. Policies that address other NTCFs including methane, as well as carbon dioxide emissions, must also be adopted to meet climate mitigation goals.